'Exhibits with real colour and interest': representations of the West India Regiment at Atlantic World's Fairs. (3rd July 2018) - Bennett, Melissa
ABSTRACT: Beyond their role in expanding and securing the British Empire, the West India Regiments (WIRs) were used to sell the Caribbean region to tourists and potential investors. Soldiers travelled in person and in photographic form to numerous world's fairs that brought the empire to London and major American cities such as Chicago and New Orleans. Through their representation at these events their likeness, and in some cases their actual physical presence, was showcased to a range of audiences who did not have to venture outside of their home countries for the experience. For nations such as Britain, who controlled vast empires, the fairs provided a justification for empire by showcasing the lack of development of some native peoples and the advancement of others under colonial rule through human exhibits. The WIRs were used as key examples of this progress and decorated promotional stands related to the West Indian colonies, unlike representatives of African ethnic groups who were used to populate constructed 'native villages'.